ضبط الترتيل وأثره في توثيق النص القرآني: The Exactitude of Tartil Style and Its Effects on Quranic Text Adoption - Hamawi, Adnan (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
One of the miracle signs of the Qur’an stands the guarantee of its preservation until the Day of Judgment. The preservation of the Quran, known by its characteristic sound that is reproducible, echo according to theory, and convergence of scholarship which is fulfilling a divine command; So when We recite it, follow its recitation (The Resurrection: 18). The rules regulating its tajwid (correct recitation) preserve the nature of a revelation whose meaning is expressed as much by its sound as by its content and expression. It is tajwìd that accounts for the characteristic and unique sound of the recited Quran, a sound immediately recognizable in all its contexts throughout the Islamic world. The correct recitation is transmitted orally and communicated orthographically, articulating each letter from its point of articulation, giving it its full value or the student listens to the teacher’s recitation of a phrase or verse of the ʿUthmānic codex. While the tartil concept was applied to the straightforward and private style of reciting the Quran, as well as to the comprehensive sense of ideal recitation. Thus, in order to understand the significance and effects of the exactitude of tartil style, that is, how it works on the adoption of Quranic text and why it works the way it was, this study attempt to describe in terms of the specific theoretical science, principles of recitation, intonation, as well as practices among Quranic circle. This qualitative study was conducted using content analysis methods through descriptive and comparative analysis of texts in accommodating an analysis of Quranic recitation by different levels, ethnicities, ages of huffaz (memorizers). The study found the differences in recitation or tartil style occurred throughout the Muslim world. However, the adherence of reciters or memorizers in Quranic text adoption confirms the concerted universality of Quranic discourse.